“KEKHUSUSAN” OTONOMI KHUSUS PAPUA - ACHMADY, LA (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2020)
The special autonomy policy, in additions to being associated with the aim of realizing the walfare of the community, is also to encouraged to promote a wider democratization and public service process, and also to strengthen the capacity and regional responsibility and resolving local problems with all the potential and creativity of region, which is also linked with the aim to maintain and strengthen the unitary State of the Republic of Indonesia. The meaning of “specificity” in the Papua Autonomy Act, contained 3 (three) main policies that constitute the spirit/soul of the Law, first : alignment to indigenous Papuans, creating/giving opportunities for self-development and placing them parallel/equal to other citizens in the frame of the unitary State of the Republic of Indonesia and the citizens of the word. Second : Protection of indigenous Papuans, = recognitions and legal protection of human rights and customery rights. Third : Empowerment of indigenous Papuans, = give the trust that is the manifestation they have: Community from Oriented (orientation to the real needs of local people); Community Based (based on rersources owned by local communities) and Community Managed (managed by local community from planning, implementation , control to the utilization of development outcomes). The remaining time of the implementation of OTSUS is the only 6 years long, it is the momentum to take the measures of strategy that should be taken by stakeholders both in the executive and legislative and cultural institution of indigenous Papuans. The time no longer to blame and feel right about OTSUS, the community will eventually give an assessment and give an answer to that we want to do, let us to do the best for society as our accountability on this blessed land.